2005
DOI: 10.1016/j.ejpain.2004.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for the relief of cancer‐related pain — a systematic review

Abstract: The notion that acupuncture may be an effective analgesic adjunctive method for cancer patients is not supported by the data currently available from the majority of rigorous clinical trials. Because of its widespread acceptance, appropriately powered RCTs are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(74 citation statements)
references
References 34 publications
1
73
0
Order By: Relevance
“…71 Alternative therapies, such as acupuncture, exercise training, and music, may be beneficial, although they have not been studied extensively in heart failure patients. [73][74][75] Opioids should be used as first-line agents for moderate to severe pain. Combination agents, such as oxycodone/acetaminophen, are generally not recommended because the adjuvant agents may prevent dose escalation.…”
Section: Painmentioning
confidence: 99%
“…71 Alternative therapies, such as acupuncture, exercise training, and music, may be beneficial, although they have not been studied extensively in heart failure patients. [73][74][75] Opioids should be used as first-line agents for moderate to severe pain. Combination agents, such as oxycodone/acetaminophen, are generally not recommended because the adjuvant agents may prevent dose escalation.…”
Section: Painmentioning
confidence: 99%
“…For many, traditional pain management approaches such as opioid treatment are not an optimal choice, 2 and studies have shown acupuncture has fewer side effects than pharmacological treatments. [3][4][5][6][7][8] Several systematic reviews and meta-analyses [9][10][11][12] evaluating acupuncture for pain management in cancer patients have been published. Three of these studies [9][10][11] concluded that the evidence was insufficient to support the use of acupuncture because of methodological limitations in the randomized controlled trials that were included.…”
Section: Introductionmentioning
confidence: 99%
“…A clinically important improvement (2 points on the esas) clear. Several studies of varying methodologic rigour suggest that acupuncture can potentially help manage cancer symptoms such as pain, lack of appetite, nausea, emotional distress, depression, and anxiety [13][14][15][16][17][18][19] . However, no study has focused exclusively on lung cancer patients, despite that cancer being one of the commonest in men and women alike 20,21 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of acupuncture has not yet been accepted as a standard of care in adjunctive medical treatment. The general applicability of the results from acupuncture studies to date are limited because of the use of different acupuncture techniques (for example, electrical or manual), controls (with or without comparison groups), outcome measures, needle protocols, and duration of treatment 13,15,16,27 . Most importantly from our perspective, no earlier acupuncture trials have focused specifically on lung cancer patients, despite the large numbers of patients diagnosed with lung cancer and their evident need for control of frequent, severe, and debilitating symptoms 28,29 .…”
Section: Discussionmentioning
confidence: 99%